Harmonic mean labeling of disconnected graphs. (2nd January 2016) - Jayasekaran, C.; David Raj, C.
Abstract: A graph labeling is an assignment of integers to the vertices or edges or both subject to certain conditions. In this paper we prove that some disconnected graphs are Harmonic mean graphs.